The effectiveness of core stability addition in short wave diathermy and star excursion balance exercise in improving the functional ability of chronic ankle instability among taekwondo athletes - I Dewa Gede Alit Kamayoga; A.A. Gd Eka Septian Utama; M. Widnyana; I Putu Yudi Pramana Putra (Universitas Udayana dan Diaspora Taipei Medical University, 2023)
Background: Taekwondo is based on sudden and violent attacks by the hands and feet; therefore, an injury can occur. Ankle sprains account for 15% to 20.8% of all sports injuries, and 72% of people who have experienced an ankle sprain report experiencing chronic ankle instability. Star excursion balance exercise is an exercise that increases the functional ability of the ankle. The shortwave diathermy intervention assists the ligaments' healing process as core stability exercise is necessary to activate postural control, which is a valuable component in treating chronic ankle instability. This study aimed to determine the effectiveness of adding core stability to shortwave diathermy and star excursion balance exercise in improving the functional ability of chronic ankle instability in taekwondo. Methods: The research used experimental research with a randomized pretest-posttest control group design. The technique used for sampling in this study is simple random sampling. There are two sample groups to be studied. The first group was given additional core stability through shortwave diathermy and star excursion balance exercise, and the second group was assigned the intervention of shortwave diathermy and star excursion balance exercise. The functional ability of the ankle is measured using the foot ankle disability index (FADI). There were 18 people in each group. The study was conducted three times a week for a month. Results: The results showed significant differences in the two groups with p = 0.000. However, the intervention group was better at improving the functional ability of chronic ankle instability in taekwondo with a value of p = 0.002. Conclusion: This study concludes that there are differences in adding core stability to the shortwave diathermy intervention and star excursion balance exercise in improving the functional ability of chronic ankle instability in taekwondo.